Improved beam diagnostics and optimization at ISAC via TITAN’s MR-TOF-MS - Reiter, Moritz Pascal; Ames, F.; Andreoiu, C.; Ayet San Andrés, S.; Babcock, C.; Barquest, B. R.; Bergmann, J.; Bollig, Julian; Brunner, T.; Dickel, T.; Dilling, J.; Dillmann, I.; et al. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2020)
Determination of the constituents of the radioactive ion beam (RIB) is crucial for successful experiments at low-energy RIB facilities and as such decides the fate of many experiments. Here we present the role of TITAN’s Multiple-Reflection Time-Of-Flight Mass Separator (MR-TOF-MS) and how it complements the present capabilities at ISAC-TRIUMF for yield determinations and beam delivery. This non-scanning, broadband, high-resolution mass spectrometer allows for real-time identification and quantification of all species, ranging from radionuclides with half-lives as low as a few ms to stable isotopes and molecules. In this manner it can be efficiently used to optimize RIB delivery through the ISAC mass separator for rate of the species of interest or its ratio to contamination. We present an example of this optimization approach, where the purity of secondary beams of neutron-rich titanium was improved by more than one order of magnitude based on the diagnostics capabilities of the new MR-TOF-MS and thus, allowed for high-precision mass measurements at TITAN.